Development of Android-Based Interactive Multimedia for Learning Topeng Tunggal Betawi Dance for Students of Dance Education Study Program, Jakarta State University - Irsyad Naufal Harits; Dwi Kusumawardani; Dinny Devi Triana (Universitas Negeri Semarang, 2023)
The research aims to develop learning materials for Topeng Tunggal dance in Betawi Dance course, using interactive multimedia to optimize students' knowledge and skills. This type of research is R&D (Research and Development), using the ADDIE development procedure. The research subjects were students of class 2021. Research data collected by observation, interviews analyzed qualitatively and questionnaires quantitatively. The results of the expert test stage obtained an average score from material experts of 3.53, meaning